2020
DOI: 10.1080/14786419.2020.1841188
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke (Cynara cardunculus var. scolymus L.) by-products as a source of inulin: how to valorise an agricultural supply chain extracting an added-value compound

Abstract: This study is aimed at valorizing artichoke (Cynara cardunculus var. scolymus L.) by-products as source of inulin, a fiber showing relevant prebiotic properties, through the realization of a waste value chain. Starting from artichoke by-products, the inulin fraction was assessed both in terms of total amount and degree of polymerization as a function of the harvest season and storage conditions. These parameters have been found significant at influencing inulin yield of extraction. For the first time, artichok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Fructan 1exohydrolases (1-FEHs) mediates degradation of inulin by eliminating terminal fructose with the formation of lower-DP inulin (Kusch et al 2009). Remarkably, the concentration and the inulin pro le as DP, vary greatly among species (Vergauwen et al 2003); however, inulin molecules with a chain length up to 200, which is the highest degree of polymerization of inulin molecules known in plants, have been found in artichoke (Lattanzio et al 2009;Cavini et al 2020). Recently, it was also demonstrated that long chain inulines (DP 10-60) exert higher immune response in humans than oligosaccharide of DP < 25 (de…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Fructan 1exohydrolases (1-FEHs) mediates degradation of inulin by eliminating terminal fructose with the formation of lower-DP inulin (Kusch et al 2009). Remarkably, the concentration and the inulin pro le as DP, vary greatly among species (Vergauwen et al 2003); however, inulin molecules with a chain length up to 200, which is the highest degree of polymerization of inulin molecules known in plants, have been found in artichoke (Lattanzio et al 2009;Cavini et al 2020). Recently, it was also demonstrated that long chain inulines (DP 10-60) exert higher immune response in humans than oligosaccharide of DP < 25 (de…”
Section: )mentioning
confidence: 99%
“…To evaluate the mono-disaccharides and fructans content, supernatant and resuspended pellets were evaporated to dryness (Cavini et al, 2020).…”
Section: Mono-disaccharides and Fructans Extractionmentioning
confidence: 99%
“…The varieties of artichoke differ both morphologically and in the content of secondary metabolites [ 6 , 7 , 8 ]. The main biomolecules contained in the artichoke are caffeoylquinic acids, such as cynarin and chlorogenic acid, flavone glycosides, inulin sugars, and minerals [ 9 , 10 , 11 ]. They contribute to the health-promoting effects on humans and there are known, different studies that show the use of artichoke as antilipidemic, diuretic, anti-inflammatory, and hepatoprotective [ 12 ], making it a “functional food” with interesting pharmacological and nutraceutical activities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these by-products are high in many phytochemicals similar to those of its edible flower heads including phenolic compounds, [ 14 , 15 , 16 ], inulin [ 17 ], and dietary fibre [ 18 ]. Based on interest in renewable resources of pharmaceutically active biomolecules, many investigations have been conducted on recycling and the optimisation of the downstream processes for maximal exploitation of artichoke biowastes [ 10 , 19 , 20 , 21 , 22 , 23 ]. However, most of these studies have focused their attention mainly on the bracts, giving little importance to the leaves which, although to a lesser extent, represent a huge waste.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main interesting strategies to ennoble minor crops consists in the extraction of bioactive molecules by using chemical or biotechnological processes with low environmental impact [5,6]. In the case of the presence of residual biomasses after processing, these are mostly used to produce energy, which is a low-added value product usually obtained starting from abundant biomasses to compensate costs and market requirements.…”
Section: Introductionmentioning
confidence: 99%